Research Assessment of Climate Change Data: A Scientometric Construct - Husain, Shabahat; Mushtaq, Muzamil (Qualitative and Quantitative Methods in Libraries; 2015: Special Issue: Bibliometrics, 2017)
As we perceive it in the contemporary sense, we smell that climate change is the buzz blemish of research for governmental agencies, research institutes, academics in general and environmentalist in particular.  There are vibrant and prominent climatic changes occurring all around the globe as can be visualized by the volume of research output produced in different corners of the world and the attention towards these arenas lead to many specialized researches to conduct the assessment and evaluation of the data produced. The present study analysed the climate change data in the last five years (2009-2013) as produced in the field of environmental science and ecology. The source of data used for the study is Web of Science and it was found that about 17, 266 publications are produced in the field from different researchbased institutes around the globe.  The published data were highest in the year 2013 i.e., 4788 number of publications, and the lowest was that of the year 2009 i.e., 2238 publications. The highest number of publications was produced from USA followed by England. W. Thuiller followed by P. Smith were the most prolific authors in the field of climate change. The articles were the most widely used document forms followed by reviews.  The prolific journals were Climatic Change and Global Change Biology. The study also assessed the citation patterns received by these articles and provides a comprehensive outline of the different aspects of the citations including the average, self and unique citations received.